Kerajaan Singosari : Jejak Penting dalam Pemerintahan Pulau Jawa - Arfan, Am'mar Abdullah (IAIN Syekh Nurjati Cirebon, 2023)
The establishment of the Singosari Kingdom in East Java represents a significant period of Indonesian history. Founded by Ken Arok, the Singosari Kingdom possessed a distinct system of government. The narrative is intricate and involves episodes of violence instigated by Ken Arok, the kingdom’s founding monarch who eliminated Tunggul Ametung. This study employs a historical research method by meticulously analyzing documents and various sources regarding past events. The Singosari government prioritizes the concepts of love for the homeland and dedication to serving the people, while earnestly striving for prosperity. This data provides valuable insights into the current state of governance and leadership, with the goal of achieving the welfare of the people and the success of the country.